Peningkatan Partisipasi Relawan dan Pelaku Pariwisata dalam Pengelolaan Risiko Bencana di Kompleks Candi Borobudur - Khaerunnisa, Khaerunnisa; Cininta, Mutiara; Handarkho, Yonathan Dri (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2022)
Disaster Risk Management Plan in cultural heritage areas such as the Borobudur Temple Complex, should be the joint responsibility of all stakeholders. In fact, disaster management at the Borobudur Temple Complex, especially the preservation of the site against disasters, is only the responsibility of the Borobudur Conservation Center. Therefore, in September-November 2021 through the research activities funded by UNESCO, UAJY and BKB have formulated a draft Disaster Risk Management Plan in the form of the borobudur-drr.id digital platform. However, due to the limited implementation time, this platform has not been fully socialized by all stakeholders. Based on the stakeholder meeting, it is known that there are differences in understanding among stakeholders in understanding the comprehensive approach contained in the Disaster Risk Management Plan Action Plan for the Borobudur Temple Complex. The diversity of educational backgrounds, experiences and exposure of stakeholders to disasters and their management requires a forum for equalizing perceptions that supports the synergy of stakeholders in supporting, supervising and implementing the action plans that have been prepared. Conservationists, volunteers and tourism actors are three of the fifty-three stakeholders that have been mapped in the Borobudur Temple Compounds Disaster Risk Management Plan, which has a vital role in realizing the action plan in the Borobudur Temple Area.